Misi, Kepemimpinan, Budaya, Kinerja, dan Visi sebagai Tulang Punggung dari Model Organisasi yang Efektif - Riyono, Bagus (Universitas Islam Indonesia, 2022)
Organizational models can be used as guidelines for understanding organizations. However, the terms used in the academic world are often not the same as the terms used in the practical world. The lack of consistency of these terms causes these organizational models to be regarded as simply unscientific models. This research was conducted to formulate an integrative concept of organization. This concept will be able to accommodate the terms of the academic world as well as the practical world, so it is expected to be able to standardize the terms in an organizational model. The research method used was the qualitative method, namely meta-ethnography. Meta-ethnography is an approach taken to synthesize some texts and research findings and then reinterpret these texts. The data analyzed in this study is the formulation of organizational models that are well known in the literature, namely the 7-S Model from Pascale and Athos (1981), the Six-Box Model from Weisbord (1976), and the Stream Organizational Model from Porras (1987). The result of the research is the discovery of 12 elements within the organization that systemically have the backbone and the related stuffs. The 12 elements can essentially be condensed into five components which is the backbone of an organization. The backbones of the organization are mission, leadership, culture, performance, and vision. Among the five elements of the backbone, the most complex one is organizational culture, which includes eight interrelated and interdependent elements. The eight elements that build the culture are values, strategy, structure, system, goals, people, skills, and style. In addition, there are environmental forces that influence the running of an organization, they are politics, competition, technology, and population.